Pengaruh Budaya Organisasi dan Kinerja Mahasiswa terhadap Motivasi Belajar di Lingkungan Kampus - Indah Fitriani; Munawaroh Munawaroh (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The background of this research is the importance of a supportive organizational culture and optimal student performance to increase learning motivation. The research aims to analyze the influeance of organizational culture and student performance on learning motivation in higher education. The method used was quantitative with a survey of 50 students in Serang City. Data was collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests, and multicollinearity tests. The results of the normally test showed that the data were normally distributed (Asymo.sig. 0.200), ith no signs of multicollinearity (tolerance 0.867; VIF 1.154). The analysis shows that organizational culture and student performance have a positive and significant effect on learning motivation. In conclusion, both play an important role in increasing motivation to study in college.